Malaysian community pharmacistsʼ perceptions of and barriers to the first year of mandatory continuous education: a nationwide exploratory study - Elsayed, Tarek Mohamed Ali; Jamshed, Shazia Qasim; Elkalmi, Ramadan Mohamed Mahmod; Alshami, Abdulkareem Mohammed; Shamsudin, Siti Hadijah; Othman, Noordin (Elsevier Ltd., 2015)
Background: Continuous professional development (CPD) is essential to keep pharmacists updated and improve the quality of patient care. The positive impact of CPD on different aspects of pharmacy practice has been documented. Despite its mandatory implementation for Malaysian pharmacists working in the private sector, there is paucity of data to explore pharmacists' perceptions to this new policy and their participation in CPD activities. Objective: To assess the community pharmacists' knowledge, perceptions of current CPD requirements and their involvement in the process. Setting: Community pharmacies in Malaysia were included. Method: A self-administered anonymous questionnaire was mailed to all community pharmacies in Malaysia. Results: Response rate was 18.7%; 87.9% of respondents showed knowledge of current CPD requirements. The majority agreed that CPD is essential, that the current CPD requirements are adequate to keep them updated, that their participation in CPD events is reflected in their pharmacy practice, and that making CPD mandatory motivates them to participate. Only 36.0% of respondents agreed that the currently available CPD resources are adequate and 49.4% found that the CPD target is achievable. Interesting topics ranked first among motivators to attend face-to-face CPD events and overlap with work schedule ranked first among barriers. The most preferred CPD content area was innovations in disease management. Mandatory CPD policy resulted in a significant increase in the mean CPD points accumulated by respondents. Conclusion: The majority of community pharmacists showed enthusiasm to CPD and perceived it positively. Many factors should be considered to make CPD more accessible for them.